NEED FOR SIGNS ON THE SEGARA ANAKAN RIVER, CILACAP REGENCY - Febriansyah; Ilham, Chairul Insani; Nurrokhim, Dion Amir (Meteor STIP Marunda, 2024)
The Segara Anakan River is a shipping channel with a channel length of 17.8 miles that serves the Seleko – Kampung Laut Route in Cilacap Regency. The condition of shipping flows in Segara Anakan is irregular due to the lack of river signs as a means of regulating traffic to create safe, secure and smooth river transportation. This research aims to determine the number of river signs needed and evaluate existing river signs. This research was carried out by reviewing field conditions and then conducting qualitative descriptive analysis in accordance with Perditjenhubdat Number: KP. 4755 / AP005 / DRJD / 2020 concerning Technical Guidelines for River and Lake Signs. Conditions in the field are that the number of signs installed is 5 compared to the supposed number of 9. The research conclusion is that the number of river signs needed in the Segara Anakan channel is 25 signs with details of 6 prohibitive signs, 3 mandatory signs, 2 warning signs. The required river signs must meet technical specifications in accordance with applicable regulations both in terms of size of sign leaves, sign poles and manufacturing materials.